ASSESSMENT OF FINANCIAL MANAGEMENT PRACTICES ON A COMPANY’S FINANCIAL PERFORMANCE: A CASE OF HWANGE COLLIERY COMPANY (HCC) - Bunyod Usmonov (Scholar Express Journals, 2024)
The aim of the study was to examine how financial management practices influence the financial performance of an organization. This investigation was motivated by the company's decreasing profitability despite attempts to implement cost-saving measures. Consequently, the research scrutinized the effects of existing practices in managing working capital, fixed assets, capital structure, and investments. The study utilized a descriptive research design and adopted a quantitative research approach. The population consisted of the 46 administrative personnel at Hwange Colliery Company (HCC), with a sample size of 30. A structured questionnaire survey was conducted. Regression analysis and Pearson correlation coefficient were employed to assess the relationship between financial performance factors and financial management practices. The findings revealed a significant impact of financial management strategies on the company's financial performance. To enhance resource efficiency, the study suggests improving accounts receivable management and ensuring sound investment decisions to mitigate potential losses
Keywords: Financial Management Practices; Fixed Assets Management; Capital Structure